Examining mortality risk prediction using machine learning in heart failure patients - Hussain, Mohammad Khalid; Wani, Sharyar; Ibrahim, Adamu Abubakar (IIUM Press, 2025)
Heart failure is fatal. Signs and symptoms of heart failure often overlap with those of other medical conditions. These symptoms could kill the patient. Predicting heart failure mortality helps healthcare workers spend resources to reduce or prevent deaths. Demographics, laboratory tests, and vital signs were used to create and test prediction models. This study compares random forests, and support vector machine to determine the best mortality risk prediction approach. This study analyses heart failure symptoms to identify risk factors for mortality. The study also examines how these findings apply to all heart failure patients. The study collects a subset of MIMIC-III heart failure patients to achieve this goal. Previous research studies used a smaller dataset, which is compared to this one. The experimental examination of blood creatinine, ejection fraction, and binned age shows that machine learning is be able to classify heart failure patients by mortality risk. This information helps clinicians improve treatment, improving patient outcomes and resource allocation. The study shows that machine learning can improve heart failure mortality risk prediction by using large clinical datasets like MIMIC-III. This study advances predictive analytics in healthcare, giving valuable information for clinicians and academics seeking to better heart failure patient care.